Towards a local model of management regarding climate change - Schlack Soto, Miguel Felipe (Revista de Sociología, 2019)
This work characterize the reflexivities in which the municipalities, integrating the Chilean Municipalities Network against Climate Change in the Metropolitan Region, construct about the consequences regarding climate change in their respective territories. The empirical evidence, gathered by semi-structured interviews, and examined through Content Analysis, deliver results that the municipal impressions regarding the socio-environmental phenomena, and their ways to approach it, are determined by the particular effects produced inside the different areas, along with Environmentalism and Ecologism as models of meaning. Likewise, evidence showed the existence of weak convergences between Municipalities and Central Government Institutions, and also that Climate Change deepens the socio-territorial inequalities already existent in the Metropolitan Region.